Estimating the Efficiency of Information Technology for Domain-Specific Mathematical Modelling - Mezhuyev, Vitaliy; Mazlina, Abdul Majid; Ravi, Samikannu (2015)
The paper analyses the efficiency of the Information Technology (IT) for Domain-Specific Mathematical Modelling (DSMM). IT DSMM was developed to meet the shortcomings of the IT for Domain-Specific Modelling (DSM). IT DSMM allows us to develop metamodels in the different mathematical semantics and thus to increase the level of adequateness of models to the modelled domains. It also reduces an amount of operations needed for the development of metamodels and models of software systems. The optimization problem of choosing the most effective IT by selection and comparison of the multiple features inherent to DSM, DSMM and GPM (General Purpose Modelling) is solved.